An analysis of the last 20 years of the American Heart Association protocols: What has changed in the basic life support? (Research, Society and Development, 2021)
Objective: Describe the main changes in Basic Life Support - BLS, over the 20 years of the American Heart Association guidelines for cardiopulmonary resuscitation in adults. Methodology: Qualitative research of a socio-historical nature of the guidelines published by the American Heart Association in the last 20 years, the treatment of the data took place through content analysis. Results: From the analysis of the documents, the subsequent changes were observed: ABCD to CAB algorithm in 2010; the compression frequency, which in 2015 became at least 100 and at most 120 per minute; the depth of compression, which, in the same year, became at least 5 cm and at most 6 cm, in adults. The implantation of Continuous Cardiac Compression, a single compression-ventilation relationship. Conclusion: It is very common to follow errors due to a lack of updating when updating protocols. Effective permanent education is essential to keep the professional updated and aware of the justification for carrying out the procedure, knowledge allows the professional to think critically, which facilitates decision-making.